Austin Bradford Hill: simply the best - Roberto Bucci; Vittoria Colamesta; Giuseppe La Torre (Epidemiology, Biostatistics and Public Health)
Austin Bradford Hill was born on July 8, 1897, third son of Sir Leonard Erskine Hill, a distinguished medical physiologist, Professor of Physiology at The London Hospital. He grew up in an upper class Victorian family.  Sir Leonard, who created an ingenious instrument for blood pressure measuring, had a deep influence on his son. In fact, Bradford decided to follow his father example. He attended Chigwell Grammar School, which was established in 1629, but unfortunately, Bradford’s decision to join the Faculty of Medicine coincided with a really big event: First World War. Bradford entered British naval aviation and...